2017
DOI: 10.1051/0004-6361/201629570
|View full text |Cite
|
Sign up to set email alerts
|

Relics in galaxy clusters at high radio frequencies

Abstract: Aims. We investigated the magnetic properties of radio relics located at the peripheries of galaxy clusters at high radio frequencies, where the emission is expected to be free of Faraday depolarization. The degree of polarization is a measure of the magnetic field compression and, hence, the Mach number. Polarization observations can also be used to confirm relic candidates. Methods. We observed three radio relics in galaxy clusters and one radio relic candidate at 4.85 and 8.35 GHz in total emission and line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(126 citation statements)
references
References 68 publications
9
111
6
Order By: Relevance
“…We compare our flux density measurements with values obtained with single dish observations that do not resolve out flux of extended sources. At 4.8 GHz, we measure a flux density of 83±8 mJy which is higher than the measurement with Effelsberg at 4.85 GHz, namely 68 ± 5 mJy (Kierdorf et al 2017). However, they noted that their value is possibly too low because of the insufficient size and low quality of the radio map.…”
Section: Flux Density Measurementscontrasting
confidence: 67%
See 2 more Smart Citations
“…We compare our flux density measurements with values obtained with single dish observations that do not resolve out flux of extended sources. At 4.8 GHz, we measure a flux density of 83±8 mJy which is higher than the measurement with Effelsberg at 4.85 GHz, namely 68 ± 5 mJy (Kierdorf et al 2017). However, they noted that their value is possibly too low because of the insufficient size and low quality of the radio map.…”
Section: Flux Density Measurementscontrasting
confidence: 67%
“…Out of these five mentioned relics, a spectral steepening has been detected between 2-5 GHz for three relics, namely the Sausage relic, the relic in A2256, and Bullet cluster. In contrast to this, some authors reported no steepening in the integrated spectrum for the Sausage relic (Kierdorf et al 2017;Loi et al 2017). Fig.…”
Section: Integrated Radio Spectra Of the Toothbrushmentioning
confidence: 75%
See 1 more Smart Citation
“…The squares at low frequencies are the observational data given in Table A1 of Stroe et al (2016). The two squares at 4.85 and 8.35 GHz are fluxes in Table 5 of Kierdorf et al (2017), multiplied by a factor of 0.71. The error bars are given in the same tables.…”
mentioning
confidence: 99%
“…This argument seems to strongly contend the DSA scenario for the origin of the relativistic electron population necessary to produce RR emission. In addition, (35) recently found that the spectral index measured in several relics is not what is expected from the DSA theory, where…”
Section: Correlation Between Mach Number and Relic Radio Powermentioning
confidence: 94%